Performance of table tomato plants with irrigation shifts associated with rooting agent doses - Giroldo, Laura Bernardino Fernandes; Silva, César Antônio da; Silva , Cícero José da (Comunicata Scientiae, 2024)
This study aimed to evaluate the development and production of table tomato plants, cultivar BSDS0005, in a protected environment, using different irrigation schedules and doses of the rooting agent Raizal®. The experiment was conducted in a greenhouse at the Instituto Federal Goiano - Campus Morrinhos from June to October 2021. The design was randomized blocks with three replications arranged in a split-plot scheme, with three irrigation shifts (1, 2, and 3 days) in the plots and five doses of Raizal® rooting agent (0, 5, 10, 15, and 20 g plant-1) in the sub-plots. 14.5 L pots of soil were used, arranged in double rows, 0.4 m between pots, 0.45 m between single rows, and 1.15 m between double rows. A drip irrigation system was used, with 2 L h-1 self-compensating emitters. Irrigation was managed by replenishing 100% of the crop evapotranspiration in each irrigation shift. The results show that the Raizal® was efficient at a dose of 10 g plant-1, with better performance in flower abortion rate and yield. The two-day irrigation shift showed better performance in terms of root dry mass (18.14 g root-1), flower abortion rate (57.41%), yield, and water use efficiency (0.077 m3 kg-1 of fruit).